Risk factors for right colon, left colon and rectal cancers differ between men and women: the population‐based HUNT study in Norway - Brenne, Siv S.; Ness‐Jensen, Eivind; Edna, Tom‐Harald; Lydersen, Stian; Laugsand, Eivor A. (Colorectal disease, 2023)
Aim The aim of this study was to assess established risk factors for colorectal cancer (CRC) separately for right colon, left colon and rectal cancer in men and women. Method This was a prospective cohort study comparing incidental CRC cases and the general population participating in a longitudinal health study in Norway (the HUNT study). Results Among 78 580 participants (36 825 men and 41 754 women), 1827 incidental CRCs were registered (931 men and 896 women). Among men, the risk of cancer at all locations increased with age [HR 1.46 (1.40–1.51), HR 1.32 (1.27–1.36), HR 1.30 (1.25–1.34) per 5 years for right colon, left colon and rectal cancer, respectively] and the risk of left colon cancer increased with higher body mass index [HR 1.28 (1.12–1.46) per 5 kg/m2]. The risk of right colon cancer (RCC) increased with smoking [HR 1.07 (1.04–1.10) per 5 pack years]. Among women, the risk of cancer at all locations increased with age [HR 1.38 (1.34–1.43), HR 1.23 (1.19–1.27), HR 1.20 (1.16–1.24) per 5 years] and smoking [HR 1.07 (1.02–1.12), HR 1.07 (1.02–1.12), HR 1.10 (1.05–1.17) per 5 pack years] for right colon, left colon and rectal cancer, respectively. The risk of RCC increased with night shift work [HR 1.93 (1.22–3.05)]. Conclusion The risk factors for developing CRC differ by anatomical location and sex. The relationship between risk factors and CRC may be more nuanced than previously known.